Separation of Radiogallium from Zinc Using Membrane-Based Liquid-Liquid Extraction in Flow: Experimental and COSMO-RS Studies. Issue 5 (29th July 2019) - Pedersen, Kristina Søborg; Nielsen, Karin Michaelsen; Fonslet, Jesper; Jensen, Mikael; Zhuravlev, Fedor
ABSTRACT: A switch from batch to continuous manufacturing of gallium-68 ( 68 Ga) and 68 Ga-labeled pharmaceuticals can be advantageous, as it recycles isotopically-enriched zinc-68 ( 68 Zn), removes pre- and post-irradiation target manipulations, and provides scalability via dose-on-demand production. Herein we report efficient extraction of radiogallium ( 66, 67, 68 Ga = *Ga) from ZnCl2 /HCl solutions in batch and in flow using a membrane-based liquid-liquid separator. From 5.6 M ZnCl2 /3 M HCl, a 1/2 (v/v) diisopropyl ether ( i Pr2 O)/trifluorotoluene (TFT) solvent extracts 76.3 ± 1.9% of *Ga and 1.9 ± 1.6% of Zn in flow using a single pass through. From 1 M ZnCl2 /6 M HCl, a 1/2 (v/v) n -butyl methyl ether ( n -BuOMe)/TFT solvent extracts 95.7 ± 2.0% of *Ga and 0.005 ± 0.003% of Zn in flow. TFT plays a key role in controlling the interfacial tension between the aqueous and the organic phases, ensuring clean membrane-based separation. The process did not extract Cu, Mn, and Co but did extract Fe. Using HGaCl4 and ZnCl2 as the extractable species, the COSMO-RS theory predicts the solvation-driven extraction of Ga and Zn with a mean unsigned error of prediction of 4.0% and 3.4% respectively.